Terapi Su Jok terhadap Penurunan Nyeri Kepala Pasien Hipertensi sebagai Upaya Antisipasi Kegawatdaruratan Kardiovaskuler - Trilia Trilia; Suzanna Suzanna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of Su-Jok therapy on reducing pain intensity in hypertensive patients at the Harapan Kita Elderly Social Institution. The type of research used in this study is a quasi-experimental design with a non-equivalent control group design. The results of the Wilcoxon test after administration of su seat therapy showed that the p-value was (0.000). In conclusion, there is an effect of su-jok treatment on reducing headaches in hypertension patients at the Harapan Kita Elderly Social Institution in Palembang. Keywords: Hypertension, Headache, Su Jok Therapy